Purulent meningitis - Bittencourt, José Mário Tacques (Revista de Medicina, 1963)
Success in the treatment of bacterial meningitis depends upon the observance of three rules. The first determines the early start of treatment. The clinicai diagnosis in patients over one year of age and who have had no previous medication is easy, because of the presence of infectious, hypertensive intracranial and antalgic radicular syndromes. In children of less than one year of age the diagnosis is difficult owing to the lack of any sign or group of signs which, for their constancy, may serve as basis for reasoning. In such cases it is advisable to make an examination of the cerebrospinal fluid whenever a severe infectious process remains undiagnosed after three days of development. It is the examination of the cerebrospinal fluid which settles the diagnosis of bacterial meningitis: hypercytosis with inversion of the leucocytic formula, lowering of the chloride and glucose contents, and the possible presence of the germ in the bacterioscopic examination or culture.The second rule determines the use of antibiotics and chemotherapy insufficient doses to rapidly reach therapeutic leveis. Before obtaining the antibiogram and choosing the specific therapeutic agent, it is advised to use sulfadiazine, 0.2 g per kg of body weight daily, penicillin 1 to 2 million units every 3 or 4 hours, and chloroamphenicol, 0.5 to 1.0 g every 12 hours. The use of the intrathecal route is advisable in cases where one wishes an immediate reaction to the medication and when it is not advisable to wait for the 6 to 8 hours necessary for therapeutic leveis in the cerebrospinal fluid being reached.The third rule determines the duration of treatment until the infectiousagent is completely eliminated. Medication should be discontinued only when all signs, both clinicai and laboratorial, indicate that the infection has been eliminated.